Crystallographic inversion-mediated superparamagnetic relaxation in Zn-ferrite nanocrystals - Ranajit Sai; Sarath Arackal; R. D. Ralandinliu Kahmei; Navakanta Bhat; Masahiro Yamaguchi; S. A. Shivashankar (AIP Advances, 2020)
Crystallographic inversion induced shift of resonance frequency in zinc ferrite nanoparticle (ZF-NP) samples is studied here. ZF-NP samples were synthesized by a solution-based, low-temperature (<200 °C), microwave-assisted solvothermal (MAS) process. Owing to the far-from-equilibrium processing condition, the MAS process produces a very high degree of crystallographic inversion, δ=0.61, in the as-synthesized nanocrystallites. A rapid thermal annealing (RTA) technique was adopted to tune-down crystallographic inversion without altering the crystallite sizes in annealed samples. The crystal structures, particle shapes, and compositions of the nanocrystalline samples were characterized by XRD, SEM and Raman spectroscopy. The samples are phase-pure, with particle size in the range 8-16 nm and their compositions are stoichiometrically accurate. The resonance phenomena in 1 to 10 GHz frequency range was measured by analyzing the impedance mismatch of a microstrip line with the magnetic material loaded on to it. The RTA protocol enables tuning of the resonance phenomena in the ZF-NC samples above 6 GHz with tunable range of ∼500 MHz